Association of SSRI and SNRI use with incidence of cardiovascular events in veterans with giant cell arteritis and polymyalgia rheumatica - Tianyu Zhang; Chris A. Gentry; Nicole M. Kuderer; Gary H. Lyman; Gary H. Lyman; Bernard Ng; Despina Michailidou; Despina Michailidou (Frontiers in Immunology)
The leading cause of death in patients with giant cell arteritis (GCA) and polymyalgia rheumatica (PMR) is cardiovascular disease. The objective of this study was to determine whether the use of selective serotonin reuptake inhibitors (SSRI) and serotonin norepinephrine reuptake inhibitors (SNRI) in veterans with GCA and PMR could have a cardio-modulatory effect as compared to nonuse. Patients with GCA and PMR were identified through the Veterans Affairs Informatics and Computing Infrastructure. After a 2:1 propensity score matching for SSRI or SNRI users, we identified nonusers with similar covariates. We then applied a multivariate logistic regression (MLR), to calculate the odds ratio (OR) for cardiovascular event (CVE) outcomes within 5 years after the index date. Related hazard ratios (HR) were also calculated to validate the discovery of our findings. We identified 2249 patients with GCA and 3906 patients with PMR. Among patients with GCA, 174 (27%) SSRI users had incident cardiovascular disease as compared to 47 (28%) SNRI users and 277 (19%) nonusers; in the PMR cohort, 108 (13%) were SSRI users compared to 71 (15%) SNRI users and 255 (11%) nonusers. The adjusted ORs of the CVE outcome associated with venlafaxine (2.44, p=0.01) and sertraline (1.45, p=0.04) were significantly greater than 1 in GCA, with similar results observed in the PMR cohort (2.01, p=0.02, and 1.45, p=0.04, respectively). Cox-regression analysis was also conducted, and the hazard ratios were qualitatively consistent with the MLR analysis. In conclusion, the adjusted risk of CVE in patients with GCA or PMR using either venlafaxine or sertraline was higher than that in the non-exposed groups.